Guided inquiry with Moodle to improve students’ science process skills and conceptual understanding - Saidil Mursali; Utami Sri Hastuti; Siti Zubaidah; Fatchur Rohman (Institute of Advanced Engineering and Science, 2024)
This study aims to improve and describe science process skills (SPS) and conceptual understanding (CU) college students through guided inquiry learning with Moodle (GI-Moodle). This quasi-experimental study used a pretest-posttest non-equivalent control group design. College students taking general biology courses at Faculty of Applied Science and Engineering (FSTT), Universitas Pendidikan Mandalika (UNDIKMA) participated in this study. They were divided into three classes: the experiment, control 1, and control 2. Their SPS was measured using an essay test instrument containing 18 items, while the CU was examined using 50 items multiple choice test and 5 items essay test. The obtained data were analyzed using the analysis of covariance (ANCOVA) test. The analysis results identified different average students’ SPS and CU before and after they attended the learning processes using GI-Moodle, guided inquiry with WhatsApp group (GI-WAG), and structured inquiry with WhatsApp group (SI-WAG). The experiment class attended learning using GI-Moodle presented a more significant increase of SPS and CU than the students attending the other two learning with GI-WAG and SI-WAG. Therefore, the GI with Moodle learning can be used to improve students’ SPS and CU during post COVID-19 pandemic. Besides, further studies are suggested to use a more number and broader participants and identify the influence of GI-Moodle on other variables.